1992
DOI: 10.1056/nejm199204303261804
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality in Patients with Cystic Fibrosis

Abstract: Patients with cystic fibrosis should be considered candidates for lung transplantation when the FEV1 falls below 30 percent of the predicted value. Female patients and younger patients may need to be considered for transplantation at an earlier stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
569
4
27

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 923 publications
(627 citation statements)
references
References 16 publications
27
569
4
27
Order By: Relevance
“…Nevertheless, our study highlights the major importance of pulmonary disease in malnutrition, but also the implication of PI and gastroesophageal reflux. Longitudinal studies demonstrated that the decline of lung function and undernutrition are related with each other (Corey et al, 1988;Kerem et al, 1992;Schoni & CasaultaAebischer, 2000) and that malnutrition may be expected to increase with advancing age (Nir et al, 1996;Steinkamp & Wiedemann, 2002). However, we observed that age and BMI were positively correlated and that patients with a severe malnutrition were significantly younger than the other patients.…”
Section: Abstract: Cystic Fibrosis; Malnutritionmentioning
confidence: 43%
“…Nevertheless, our study highlights the major importance of pulmonary disease in malnutrition, but also the implication of PI and gastroesophageal reflux. Longitudinal studies demonstrated that the decline of lung function and undernutrition are related with each other (Corey et al, 1988;Kerem et al, 1992;Schoni & CasaultaAebischer, 2000) and that malnutrition may be expected to increase with advancing age (Nir et al, 1996;Steinkamp & Wiedemann, 2002). However, we observed that age and BMI were positively correlated and that patients with a severe malnutrition were significantly younger than the other patients.…”
Section: Abstract: Cystic Fibrosis; Malnutritionmentioning
confidence: 43%
“…There have been previous studies that have employed proportional hazards modelling in order to identify measurements that are of prognostic value in these patients, with particular emphasis on the use of lung function measurements to determine life expectancy. KEREM et al [2] studied the survival of 673 patients (children and adults) from the Hospital for Sick Children, Toronto, over a 13 yr period (1977卤1989). Twenty-eight per cent of the patients died during this time.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, the earlier referral of females and younger patients was encouraged as these patient categories have been shown to have a poorer prognosis [5]. All patients were from the UK or Eire.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The first question has been addressed by previous studies [4,5]. Current international consensus statements suggest that CF patients should be listed for transplantation when their forced expiratory volume in one second (FEV1) falls to 30% pred normal or below, as this appears to equate to a life expectancy of #2 yrs.…”
mentioning
confidence: 99%